LOCAL GOVERNMENT POSITION IN EQUITY PARTICIPATION TO BUMD, BUMN AND THIRD PARTIES - Nurasiah Harahap (Universitas Muhammadiyah Sumatera Utara, 2023)
The state in carrying out government administration activities is carried out through government institutions or is usually categorized as a public legal entity. Based on the statutory regulations, it is stated that any capital participation or additional capital participation to regional companies must be regulated in a separate regional regulation regarding participation or additional capital. Regional Government equity participation can be implemented if the amount to be included in the relevant budget year has been stipulated in a Regional Regulation. In Article 1654 of the Civil Code which reads